Multi-Component Characterization and Quality Evaluation Strategy of Sarcandrae Herba by Combining Dual-Column Tandem HPLC Fingerprint and UPLC-Q-TOF-MS/MS - Zhijian Zhong; Pan Deng; Xiaorong Luo; Weifeng Zhu; Pengdi Cui; Zhe Li; Zhiqiang Xiao; Yu Shen; Xinyu Wu (Molecules)
A dual-column tandem mode was used to establish the fingerprints of Sarcandrae herb from different origins, and their chemical compositions were characterized by UPLC-Q-TOF-MS/MS, which provided an experimental basis for the establishment of a rapid and efficient method for the overall quality control of Sarcandrae herba. For the first time, nine common components were identified from the Sarcandrae herba herbs of 24 origins, which were neochlorogenic acid, chlorogenic acid, 4-caffeoylquinic acid, eleutheroside B1, quercetin-3-O-β-D-glucuronide, neoastilbin, astilbin, isofraxidin, and rosmarinic acid, respectively. A total of 92 compounds were identified by liquid mass spectrometry. The quality of the Sarcandrae herb from 24 origins was analyzed by similarity evaluation, principal component analysis, and cluster analysis, and the chemical components of Sarcandrae herba were identified by UPLC-Q-TOF-MS/MS. The results showed that the overall analysis based on fingerprinting and mass spectrometry could differentiate the origins of the herbs.